Challenges and Countermeasures in Accounting Informatization for Small and Medium-Sized Enterprises - Jiang, Xinyu (Simen Owen Academic Proceedings Series, 2025)
With the rapid advancement of information technology, accounting informatization has emerged as a crucial strategy for small and medium-sized enterprises (SMEs) to enhance managerial capabilities, optimize resource allocation, and strengthen market competitiveness. Despite its potential, SMEs continue to encounter numerous challenges in implementing and applying accounting informatization, including weak technical infrastructure, limited financial investment, low system integration, data security vulnerabilities, and insufficient professional talent. This study employs a combination of literature review, case analysis, and questionnaire survey to provide a comprehensive assessment of the current state of accounting informatization among SMEs, systematically identifying existing issues and examining their root causes. Based on these insights, the paper proposes a series of innovative countermeasures, such as designing a tiered informatization development strategy, integrating cloud accounting and artificial intelligence technologies, enhancing data security frameworks, streamlining accounting business processes, and establishing cross-departmental information-sharing mechanisms. The findings suggest that through strategic technological investments and optimized application models, SMEs can not only significantly reduce operational costs but also achieve deep integration between business operations and financial management via data-driven approaches, ultimately securing sustainable competitive advantages in the digital economy era.